2002
DOI: 10.1086/345361
|View full text |Cite
|
Sign up to set email alerts
|

The History of Food Fortification in the United States: Its Relevance for Current Fortification Efforts in Developing Countries

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 13 publications
0
74
0
Order By: Relevance
“…Clark, Robert and Hampton 2016), and is thought to be stronger among specialised experts in a given field compared with individuals with broader areas of expertise (Tichy 2004). 2 In fact, as Bishai and Nalubola (2002) show, following the success of salt iodisation in eliminating goitre in the US Midwest in the 1920s, the championing of other forms of food fortification (notably that of wheat flour and bread with iron) was based on technocratic optimism rather than specific evidence of impact. 3 Evidence of positive impact of flour fortification programmes is, understandably, even more ambivalent than that based on trials (Hurrell et al 2010;Pachón et al 2015).…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…Clark, Robert and Hampton 2016), and is thought to be stronger among specialised experts in a given field compared with individuals with broader areas of expertise (Tichy 2004). 2 In fact, as Bishai and Nalubola (2002) show, following the success of salt iodisation in eliminating goitre in the US Midwest in the 1920s, the championing of other forms of food fortification (notably that of wheat flour and bread with iron) was based on technocratic optimism rather than specific evidence of impact. 3 Evidence of positive impact of flour fortification programmes is, understandably, even more ambivalent than that based on trials (Hurrell et al 2010;Pachón et al 2015).…”
Section: Notesmentioning
confidence: 99%
“…The processes and actions analysed by May et al (2003) in the context of health systems could easily apply to the role of champions such as the American Medical Association in the 1920s and 1930s (Bishai and Nalubola 2002), or The Lancet 2013 Nutrition Series (e.g. Bhutta et al 2013) in the current discourse on food fortification.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the nutrient content which naturally emerges, mineral and vitamin compounds are joined to foods. With a view to improving protein and/or calorie intake, a drink in the form of milkshake is given between meals three or four times a day [22,23]. It has been demonstrated that food fortification improves nutritional intake of the neurosurgical patients that often do not eat up whole meal served on their plates [24].…”
Section: Food Fortificationmentioning
confidence: 99%
“…Another early use of fortification was the introduction of vitamin D in milk. By the end of the 1930s, virtually all milk in the U.S. was fortified (5). Thiamin (vitamin B1) was first synthesized in 1936 by Robert R. Williams, and in 1942, the fortification of white flour and bread with thiamin became required by the State of South Carolina.…”
Section: Fortificationmentioning
confidence: 99%